Physical Fitness Swimming Athlete In UNSIKA - Ruslan Abdul Gani; Irfan Zinat Achmad (IKIP Budi Utomo Malang, 2020)
This study aims to determine the level of fitness conditions in the students who become athletes in swimming UNSIKA. This research used was to use a method of extracting information field (survey) quantitative research. Sampling is done using saturated sampling, meaning that the entire population is a member of the sampling. Number of samples research were 20 male students The instrument is used by referring to Norms and guidelines for assessing physical fitness levels standard for16-19 years. Results of this study that the level of physical fitness of UNSIKA swimming athletes must continue to be improved because with the level of fitness that does not match the appearance of swimming athletes will affect the results of swimming when participating in competitions at the college level, the level of physical fitness condition of swimming athletes is influenced by the adaptation of athletes accustomed to in a swimming pool that makes the results of physical fitness is not expectations at a good level of physical fitness. The conclusion of this study is the level of physical fitness conditions on students members of UNSIKA swimming are in the Medium classification.